2021
DOI: 10.1016/j.clae.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation of static and dynamic behavior of different toric silicone-hydrogel contact lenses

Abstract: The present study aimed to estimate how orientation position, recovery time, and contact lens decentration, associated with visual performance, may vary on several designs of the most recent toric siliconehydrogel toric contact lenses in two-time different moments. Methods: To evaluate the toric silicone-hydrogel toric contact lens position and stability, it was conducted with a prospective, observational, randomized, and single-center case series including 95 astigmatic eyes wearing four toric silicone-hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(81 reference statements)
0
4
0
Order By: Relevance
“… 12 , 33 , 34 The main reason for this tendency may be that the temporal corneal shape is commonly steeper than the nasal one, and the lenses tended to drift to the steeper side. 29 , 35 So, the asymmetric compression pattern observed in this study, can be attributable to inherent Ortho-k effect on asymmetric corneal surface. 36 Simple linear regression analysis showed that there was no association between vertical lens decentration and regional ET or ST changes, but there was association between post Ortho-k ET and the magnitude of horizontal lens decentration.…”
Section: Discussionmentioning
confidence: 51%
“… 12 , 33 , 34 The main reason for this tendency may be that the temporal corneal shape is commonly steeper than the nasal one, and the lenses tended to drift to the steeper side. 29 , 35 So, the asymmetric compression pattern observed in this study, can be attributable to inherent Ortho-k effect on asymmetric corneal surface. 36 Simple linear regression analysis showed that there was no association between vertical lens decentration and regional ET or ST changes, but there was association between post Ortho-k ET and the magnitude of horizontal lens decentration.…”
Section: Discussionmentioning
confidence: 51%
“…According to some research, a novel class of optically clear silicone thermoplastic hydrogel materials could be used to make contact lenses [ 180 , 181 ]. The polymers’ general formula includes a section made of silicone and produced from polyciliate that is joined by hydroxyl or amino groups [ 182 ]. In addition, among the variety of their applications in vision correction, soft contact lenses may also be utilized to administer medications to the eye [ 183 , 184 ].…”
Section: Translational Applicationsmentioning
confidence: 99%
“…Another method is ray tracing-based (Wang et al , 2022). Such methods are typically implemented in conjunction with a grid (Sánchez-García and González-Pérez, 2021), either an ordinary occupying grid or an octree grid. The basic principle is that when a laser misses a cell, the hits count adds one, and when the laser beam passes through the cell, the misses count adds one.…”
Section: Introductionmentioning
confidence: 99%